INTERACTIVE DATA VISUALIZATION FOR THE WEB - SCOTT MURRAY (MUMBAI O"REILLY SPD PVT LTD, 2022)
Interactive data visualization for the web involves creating dynamic charts, graphs, and maps that allow users to directly manipulate the data to uncover insights
COMPUTERS
CSE & CSM & CSD
Keywords: WEB DEVELOPMENT; COMPUTER SCIENCE